Explaining the Integrated Approach to Border Management and Control: A Case Study of Iranian Land Borders - reyhane salehabadi; syrus ahmadi; afshin motaghi (تحقیقات کاربردی علوم جغرافیایی, 2023)
Borders are known as places where government institutions implement their own law in a variety of ways and forms. Given the different approaches to border control and management, it can be seen that this issue is still viewed as a security issue in developing countries, including Iran, and most of the approaches related to this are from a purely security perspective. The boundary view must be multidimensional and comprehensive. In this study, we seek to answer the questions of how land border management can be done. And which of the indicators of border management is more weighty and important? Therefore, the research method is a combination of Kendall, Demetel and AHP methods. The findings of the study show that we have five main components of border management in economic, cultural-social, civil, security-military and integrated management, and each of the seven components. Using these techniques, it can be stated that indicators such as identifying and identifying opportunities and identifying their fertility factors (0.1), studying and understanding the geographical location and spatial conditions of border regions (0.099), can be determined and determined. Identifying threats and identifying their roots and factors (0.098) and excluding border areas of isolation (0.096) are the most important. Therefore, it can be concluded that border management should be considered in combination with other factors, ie the application of only one approach, such as economic or security, cannot solve the problems of the country's border regions.